2013
DOI: 10.1177/1367493512473855
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported maternal parenting style and confidence and infant temperament in a multi-ethnic community

Abstract: Ethnic minority children in the United Kingdom often experience health disadvantage. Parenting influences children's current and future health, but little is known about whether parenting behaviours and mother's perception of her infant vary by ethnicity. Using the Born in Bradford (BiB) birth cohort, which is located in an ethnically diverse and economically deprived UK city, we conducted a cross-sectional analysis of mother's self-reported parenting confidence, self-efficacy, hostility and warmth, and infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Early work from BiB suggests that consanguineous relationships, mainly seen as a risk factor for congenital anomalies, might simultaneously protect against psychosocial stress [28]. We have also found that Pakistani mothers report feeling more confident about their abilities as a parent and fewer of them adopt a hostile approach to parenting than White British women [29]. Using linked General Practice (GP) data, we have found that Pakistani mothers have a higher prevalence of undiagnosed and untreated depression and anxiety, and that these mothers have children with worse socioemotional wellbeing at age 4-5 years [6,14,30].…”
Section: Priority Research Areassupporting
confidence: 55%
“…Early work from BiB suggests that consanguineous relationships, mainly seen as a risk factor for congenital anomalies, might simultaneously protect against psychosocial stress [28]. We have also found that Pakistani mothers report feeling more confident about their abilities as a parent and fewer of them adopt a hostile approach to parenting than White British women [29]. Using linked General Practice (GP) data, we have found that Pakistani mothers have a higher prevalence of undiagnosed and untreated depression and anxiety, and that these mothers have children with worse socioemotional wellbeing at age 4-5 years [6,14,30].…”
Section: Priority Research Areassupporting
confidence: 55%
“…Higher scores indicated increasing efficacy and warmth and lower hostility. Due to skewness within these distributions, a 20th centile cutoff was used whereby those with the lowest fifth of scores were deemed to have less warmth and self-efficacy with higher hostility, as utilised previously in other BiB studies [48]. Information pertaining to socio-demographic factors including maternal age, marital status, maternal education, family size, unemployment, ethnicity and English as first language were all completed at baseline.…”
Section: Independent Measuresmentioning
confidence: 99%
“…Mexican immigrant mothers, compared with European American mothers, have reported higher levels of parenting self-efficacy, although parenting self-efficacy for this population may diminish as acculturation increases (Ceballo & Hurd, 2008;Izzo, Weiss, Shanahan, & Rodriguez-Brown, 2000). Using a large sample of mothers living in the United Kingdom, just more than half of whom were of Pakistani origin and the remainder White British, researchers found that the mothers of Pakistani origin reported more parental confidence overall (Prady, Kiernan, Fairley, Wilson, & Wright, 2014).…”
mentioning
confidence: 99%